Analisis Perbandingan Agregat Mantap Air pada Lereng Curam Tanpa Teknik Konservasi Mekanik - Norhana Norhana; Muhammad Mahbub; Abdul Haris (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
The slope is one of the important elements in topography that affects various natural processes and human activities. Slope position can lead to reduced soil fertility due to runoff. This research aims to analyze the comparison of water-stable aggregate on different slope positions which are divided into three, namely between upper slope, middle slope and lower slope. The research method used is descriptive comparative, which is carried out by deliberate sampling on sloping land planted with rubber plants with a depth of 0-20 cm and the same slope of 25-45% and then analyzed in the soil laboratory. Data were analyzed by t-test to determine the comparison of water-stable aggregate different slope positions. The results showed that water-stable aggregate values at different slope positions had significant differences. Water-stable aggregate values in the upper slope tend to be smaller than those in the middle slope and lower slope which are much larger. Slope position, organic-C content, and clay fraction affect water-stable aggregate values